SERVICE-LEARNING IN HIGHER EDUCATION: EXPERIENCES OF IMPLEMENTATION IN LITHUANIA - Gruslytė, Monika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper presents a review of the experiences in introducing service-learning as philosophy of, approach to and method of higher education in a number of universities in Lithuania over the latter years. The socio-cultural and educational adaptation of the concept that mainly originated in the USA primarily found the soil for being embedded in Siauliai University and the cases of continuing to present-day application of service-learning in Lithuanian environment of higher education as well as major approaches and principles that lead to and create unique experiences of Lithuanian higher education institutions contribute to enriching and enhancing higher education practices with students’ competences and skills in bridging theory and practice, acquiring agency that potentially leads to a positive social change.The aim of the investigation is to display the overviewed experiences of Lithuanian universities in embedding service-learning reaching for improved students’ competences and skills as well as increased social awareness and agency.The review demonstrates the experiences in adapting the concept of service-learning to European and Lithuanian socio-educational situation as well as the living need in updating, adjusting and revitalising service-learning as an educational innovation to meet the expectations set for higher education and challenges faced in real-world practice.